Tourism Communication in the Njuah-Njuah Festival: Building Cultural Identity and Local Tourism Appeal - Feronika Berutu; Virgitta Septyana; Josephine Valerie Adijaja (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to analyze tourism communication in the Njuah-Njuah Festival as a process of cultural representation that contributes to the identity construction of the Pakpak Tribe and supports nation branding of Dairi Regency through destination image development. Method: This research employs a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving local government officials, Member of the Festival Organizing Committee, traditional leaders, tourists and Local SME Owner/Business Practitioner. Data analysis was conducted using thematic analysis, including data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. Result: The findings show that the Njuah-Njuah Festival functions as a symbolic communication medium in which cultural narratives, symbols, rituals, and performances convey collective meanings, ancestral values, and local identity. The festival serves as a communicative space where cultural messages are encoded and performed through verbal and nonverbal interactions. From a Community Based Tourism perspective, local communities act as key actors in the communication and preservation of cultural values. However, tourism communication strategies are still not optimal, particularly in the utilization of digital media and the packaging of cultural narratives. Contribution: This study highlights that cultural festivals are not only tourism attractions but also communication processes that shape authenticity, identity, and destination branding. The findings imply the importance of strengthening cultural policy, enhancing digital storytelling strategies, and improving cross-sector collaboration to support sustainable and competitive cultural tourism development